Habilidade competitiva de cultivares de trigo e sua contribuição no manejo de azevém - Rockenbach, Dalvane (2014)
Three experiments were conducted in 2012, two in the field and one in the greenhouse with the objective of identifying the competitive potential of different wheat cultivars. The field experiments were conducted in Cruz Alta, RS and Vacaria, RS in the absence and presence of competition with ryegrass. In the greenhouse the wheat cultivars were sown in pots to evaluate initial growth. 2013 Cruz Alta, RS two experiments were conducted using contrasting cultivars related to the competitive potential defined in the experiments of 2012. This experiment had the purpose of evaluating the contribution of the competitive potential in chemical control of ryegrass. Five managements of ryegrass, control, weeded, herbicide application iodossulfuron-methyl at a dose of 5 g ha-1 at the beginning of tillering, herbicide application 15 days and 30 days after the start of tillering were used. Plant characteristics such as plant height, dry matter of shoots, ground cover, potential competitive ability and yield losses due to the competition, in addition to the suppression ability of the ryegrass indicate that the cultivar BRS 327 has high competitive potential with ryegrass and the variety OR 1 has the lowest competitive potential among the tested cultivars. The higher competitive potential of the cultivar BRS327 related to OR1, did not serve as an auxiliary tool in the management of ryegrass. The higher competitive potential of the cultivar Fundacep 47 compared to Fundacep 30 served as an auxiliary tool in the management of ryegrass.